Hematopoietic Chimerism and Transplantation Tolerance: A Role for Regulatory T Cells - Pasquet, Lise; Joffre, Olivier; Santolaria, Thibault; van Meerwijk, Joost (Frontiers in Immunology, 2011)
The major obstacle in transplantation medicine is rejection of donor tissues by the host’s immune system. Immunosuppressive drugs can delay but not prevent loss of transplants, and their efficiency is strongly impacted by inter-individual pharmacokinetic differences. Moreover, due to the global immunosuppression induced and to the broad distribution of their targets amongst human tissues, these drugs have severe side effects. Induction of donor-specific non-responsiveness (i.e. immunological tolerance) to transplants would solve these problems and would substantially ameliorate patients’ quality of life. It is widely believed that bone marrow or hematopoietic stem cell transplantation, and resulting (mixed) hematopoietic chimerism, invariably leads to immunological tolerance to organs of the same donor. A careful analysis of the literature, reviewed here, indeed shows that chimerism consistently prolongs allograft survival. However, in absence of additional conditioning leading to the development of active regulatory mechanisms, it does not prevent chronic rejection. A central role for active tolerance in transplantation-tolerance is also supported by recent data showing that genuine immunological tolerance to organ allografts can be achieved by combining induction of hematopoietic chimerism with infusion of regulatory T lymphocytes. Therefore, conditioning regimens that lead to the establishment of hematopoietic chimerism plus active regulatory mechanisms appear required for induction of genuine tolerance to allogeneic grafts.